Amido resistente em diversas fontes não convencionais de amido - Fontinha, C.; Correia, Paula (RE, 2010)
Resistant starch is not degraded in the small intestine, leading to a beneficial health effect like the dietetic fibre has. In this work resistant starch content was determined on flours and starches extracted from two varieties of chestnuts (Castanea sativa Mill), Longal and Martainha, and two acorn species (Quercus rotundifolia, Quercus suber). Flours were produced by milling the fruits after drying at different temperatures, 40º C, 50º C, 60ºC e 70ºC. After, starch was isolated from flours by two different extraction methods: physicochemical and enzymatic. Resistant starch content was higher on the flours obtained from the fruits dried at 60ºC, with values of 46,8%, 36,5%, 39,9% e 43,9%, respectively for Longal and Martainha chestnuts, and acorns Quercus rotundifolia, Quercus suber. The physicochemical method presented higher content of resistant starch for all the materials. It seems that drying fruits at 60ºC and the use of the physicochemical isolation method for starch from flours obtained from fruits dried at this temperature preserved better the starch integrity.
Keywords: acorns; Chestnuts; resistant starch